Dengue, Japanese encephalitis and Chikungunya virus antibody prevalence among captive monkey (Macaca nemestrina) colonies of Northern Thailand - Nakgoi K. (John Wiley and Sons Inc., 2014)
The potential of macaque Macaca nemestrina leonina in Thailand to be infected by endemic arboviruses was assessed. The prevalence of antibodies of three arboviruses actively circulating in Thailand was determined by Plaque Reduction Neutralization assay procedures using samples from captive colonies in Northern Thailand. Out of 38 macaques, 9 (24%) presented reacting antibodies against dengue virus, 5 (13%) against Japanese encephalitis virus, and 4 (10%) against Chikungunya virus. Our results indicate that the northern pig-tailed macaque in Thailand can be infected by these arboviruses, inferring therefore that their virus specific vectors have bitten them. Given that, northern pig-tailed macaque represents an abundant population, living in close range to human or in peridomestic setting, they could play a role as potential reservoir host for arboviruses circulating in Thailand. Am. J. Primatol. 76:97-102, 2014. © 2013 Wiley Periodicals, Inc.